2022
DOI: 10.3390/su14159150
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Porosity Formation in Liquid-Assisted Mechanochemical Synthesis of Metal-Organic Framework Cu3(BTC)2 for Adsorption-Based Applications

Abstract: The mechanochemical synthesis of metal-organic framework Cu3(BTC)2 was conducted with various amounts of water–ethanol liquid added prior to grinding. Using the XRD, SEM and N2 sorption results, an attempt was made to explain the mechanisms by which liquid may affect the formation of Cu3(BTC)2 and its porosity in the grinding process. The experimental results show that microporosity is controlled by the degree of crystallinity of Cu3(BTC)2 structures. Within the range of liquid-assisted grinding (LAG), it is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…23 The liquid medium in LAG and iLAG assists in the deprotonation of the linkers stabilizes intermediates and the pores of the MOF. 24,25 It has been reported that mechanochemical synthesis of MOFs can greatly reduce reaction times from several hours or days to 15 min. 26 In addition, a mechanochemical experiment by Gao et al found that up to 20 g of the MOF Zn-atz-ipa could be produced in a single batch in just 20 min.…”
Section: Introductionmentioning
confidence: 99%
“…23 The liquid medium in LAG and iLAG assists in the deprotonation of the linkers stabilizes intermediates and the pores of the MOF. 24,25 It has been reported that mechanochemical synthesis of MOFs can greatly reduce reaction times from several hours or days to 15 min. 26 In addition, a mechanochemical experiment by Gao et al found that up to 20 g of the MOF Zn-atz-ipa could be produced in a single batch in just 20 min.…”
Section: Introductionmentioning
confidence: 99%